Michel Richard Delalande engraving BNF Gallica - Henri Simon Thomassin... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Michel Richard Delalande engraving BNF Gallica. Michel-Richard Delalande (1657-1726), french baroque composer.
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons